Aldosterone levels and the -344t/C aldosterone synthase in individuals with a family history of hypertension (Bangladesh Journal of Medical Science, 2016)
Background: Genetic factors play an important role in the determination of hypertensive disease in a family. The -344T/C the aldosterone synthase gene has been reported in various populations closely related to hypertension. The aim of this study was to determine the presence of the -344T/C polymorphism of the aldosterone synthase gene and the levels of plasma aldosterone in individuals with and without a family history of hypertension.Methods: This study was a case control design, with healthy individuals with a family history of hypertension as cases (n-42) and those without a family history of hypertension as controls (n=41). The subjects plasma aldosterone levels were analysed by enzyme-link immunosorbent assay (ELISA) and the gene polymorphism was analysed by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). The data were analysed by an independent sample T-test and Chi square test, and the significance level was set at P